2015
DOI: 10.1097/mot.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Novel preservation methods to increase the quality of older kidneys

Abstract: Older kidneys are more prone to acute kidney injury during ischemic periods combined with an impaired ability to fully recover after transplantation. Novel preservation and resuscitation methods provide the opportunity to select transplantable kidneys better founded or even repair re-existing damage reducing the risk of impaired graft function and improving survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…4 In addition, convincing data are lacking, addressing underlying mechanisms of kidney graft protection by machine perfusion. 7 On the basis of this, the overall acceptance of perfusion systems for kidneys has remained relatively poor in many centers, despite the fact that the rate of delayed graft function (DGF) undoubtedly improved by machine kidney perfusion, especially in ECD grafts. 23 Recent studies, however, have triggered a clinical reinterest in kidney machine perfusion, mainly in UK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition, convincing data are lacking, addressing underlying mechanisms of kidney graft protection by machine perfusion. 7 On the basis of this, the overall acceptance of perfusion systems for kidneys has remained relatively poor in many centers, despite the fact that the rate of delayed graft function (DGF) undoubtedly improved by machine kidney perfusion, especially in ECD grafts. 23 Recent studies, however, have triggered a clinical reinterest in kidney machine perfusion, mainly in UK.…”
Section: Discussionmentioning
confidence: 99%
“…8,32 On the basis of these observations, the current clinical practice of DCD kidney perfusion may need to be adapted, being most frequently continuous cold perfusion using a pressure of (30/20 mm Hg) LifePort Kidney Transporter (Organ Recovery Systems, Chicago, IL) without active oxygenation. 4,7,31 Notably, the difference between both perfusion techniques appears multifactorial because of several varying parameters, for example, perfusate composition, temperature, pO 2 , and perfusion pressure. The results of this study therefore need to be confirmed in human by randomized trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo normothermic perfusion of grafts from ECDs offers an interesting new approach . Standard cold anoxic storage is associated with ongoing graft injury and prohibits graft assessment.…”
Section: Donor Graft Preservationmentioning
confidence: 99%
“…However, these organs show a higher risk for unfavorable outcome as they are more susceptible to ischemia reperfusion injury (IRI) (2, 3). In the need to improve organ viability and function, most notably machine perfusion has been proven to exert beneficial effects on organ preservation in a number of experimental and clinical trials (47).…”
Section: Introductionmentioning
confidence: 99%